Decentralisation and Democratisation in Local Government Focusing Key Development Programs in Bangladesh - Hossain, Abul; Habib, Ahsan (CenRaPS Journal of Social Sciences, 2021)
The local government system is considered to be the main regulator of good governance in a country. Although the local government system in Bangladesh is very old, it has tiny achievements in terms of its effectiveness, decentralisation of power, democratic practices, and public participation. After the country's independence, almost all the governments have come up with the innovation of different levels of local government structures was just nomenclature. They never allowed the local people to enjoy autonomy by their elected representatives in the way directed by the constitution. On the other hand, various local and international development partners have been implementing various programs to strengthen the local government system in Bangladesh, decentralise it and ensure public engagement in local government. Through which some positive elements have been added to the issue of autonomy and participation of the people in the local government system; however, it is significantly minor than required. This research paper seeks to understand the process of democratisation and decentralisation in the local government system of Bangladesh by fieldwork-based research knowledge and review various initiatives taken for the development of the local government system. Besides, drawing on literature and the observations and research on Union Parishad (the lowest tier of local government in Bangladesh), the interrelationship between local government elections and power structure has also been analysed in this article. Ultimately, this paper argues that the process of decentralisation and strengthening of the local government system in Bangladesh through development interventions. Though the interventions of development programs could have been mammoth achievements in the path of democratisation and decentralisation, the party politicisation has made massive impediments to attain the targets.